2010
DOI: 10.1111/j.1423-0410.2010.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

When and why is blood crossmatched?

Abstract: 2008 Serious Hazards of Transfusion data showed that 29/39 (74%) of laboratory errors resulting in 'wrong blood' occurred out of hours whilst our audit shows that only 25% of crossmatch requests are made in that time period, suggesting that crossmatching performed outside core hours carries increased risks. The reason for increased risk of error needs further research, but 25 laboratories had only one member of staff working out of hours, often combining blood transfusion, haematology and coagulation work. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A prospective study in the North of England found that only 25% of the blood demands were marked as urgent (required within 1 h). [7]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study in the North of England found that only 25% of the blood demands were marked as urgent (required within 1 h). [7]…”
Section: Discussionmentioning
confidence: 99%
“…This TS policy thus decreases the processing time in BB when an actual BT is needed. [7] Showing the advantages of TS policy vis-à-vis TXm policy, Aggarwal et al . demonstrated that the TAT could be significantly reduced by such an implementation in the Indian context also.…”
Section: Discussionmentioning
confidence: 99%
“…ABO/Rh type and screening is performed to prevent transfusion complications from incompatibility and other irregular antibodies [1] Preoperative ABO/Rh type and screening is often routinely performed in patients scheduled to undergo elective surgery with a potential need of transfusion [2,3].…”
Section: Introductionmentioning
confidence: 99%